Evaluation of the production potential of quorum quenchig enzymes of extremophile bacteria from Antarctica (2023)
Cell-cell communication mediated by the production of N-acylhomoserine lactone is one of the causes of the production of virulence factors in pathogens and biofouling. Although quorum-quenching is a useful method to disrupt quorum sensing signals, different QQ enzymes are required to block bacterial communication in specific environments. The aim of this study was to determine the QQ enzyme production potential of psychrophilic bacteria isolated from Antarctic marine sediments. This study was divided into three phases: (i) semi-qualitative evaluation of lipolytic activity, (ii) evaluation of resistance to β-lactam antibiotics, and (iii) evaluation of β-lactamase activity. In this study, the bacterial strains evaluated presented lipolytic activity and resistance to β-lactam antibiotics (ampicillin and penicillin). In addition, the strains UTB 167 and UTB 170, related to the genus Psychrobacter, presented β-lactamase activity (1.7-3.9 Umol/L), which indicates that their potential to produce QQ enzymes related to the metallo-βlactamases superfamily.